Holy Scripture and the quest for authority at the end of the Middle Ages - Levy, Ian Christopher (Reading the scriptures, 2012)
Facets of authority in the late Medieval church -- Indignant master: John Wyclif -- Ambivalent friar: William Woodford -- Fontes : Thomas Netter -- Falling out: Hussites and their Czech opponents -- Approaching final authority: Gerson and the Conciliarists -- Enduring dilemma